Persistence of clonal azole-resistant isolates of Candida albicans from a patient with chronic mucocutaneous candidiasis in Colombia (2020)
Purpose: The present article describes retrospectively a case of a patient with chronic mucocutaneous candidiasis (CMC) who presented recurrent Candida albicans infection since he was 6 months old. We obtained 16 isolates recovered during a 4-year period. Our purpose was to determinate the susceptibility, genotyping, and the pathogenicity profile in all the isolates. Methods: Sixteen C. albicans were isolated from a 25-year-old male with several recurrent fungal infections admitted to Hospital. The isolates were recovered during 4 years from a different anatomical origin. We typified them by multilocus sequence typing, also we evaluated susceptibility to fluconazole, itraconazole, voriconazole, posaconazole, isavuconazole, caspofungin, and amphotericin B by microdilution method and we also test the pathogenic capacity in the Galleria mellonella model. Results: Genotyping of all clinical isolates showed the persistence of the same diploid sequence type (DST). Isolates changed their susceptibility profile over time, but there were no significant statistical differences in pathogenicity. Conclusion: Herein, a persistent clonal isolates of C. albicans (DST 918) in a patient with CMC, showed changes in its susceptibility profile after several antifungal treatments acquiring gradual resistance to the azole drugs, which did not affect their pathogenicity. © 2020 Journal of Global Infectious Diseases